SOSIALISASI SISTEM INFORMASI PERSEDIAAN BARANG PADA UMKM BALI TIMOR JAYA - Dita Nurmadewi; Anastasya Andriarti; Zakiul Fahmi Jailani; Sigit Chairul Rochman; Muhammad Vallen Firdaus (Jurnal Abdimas Bina Bangsa, 2023)
The development of information and communication technology is getting faster and many information systems support business activities to increase business competition. Micro, Small, and Medium Enterprises (MSMEs) are one of the businesses that support economic growth and community welfare in Indonesia. Bali Timor Jaya is one of the MSMEs engaged in the garment sector which currently has several online and offline stores and one warehouse for the production and storage of goods. Bali Timor Jaya has problems related to the management of goods because it has not utilized information technology and still uses manual methods by recording incoming and outgoing products in the ledger. This problem causes several losses for Bali Timor Jaya MSMEs, especially related to informing product availability to customers. Therefore, an inventory information system was created to optimize operations and performance related to the management of goods. Service activities related to socialization are carried out to support the owner of Bali Timor Jaya to gain skills and knowledge about the features and how to operate or use a website-based inventory information system